Building Sustainable Competitive Advantage In the Academic Environment of Private Higher Education In Bali - Sitiari, Ni Wayan; Sariani, Ni Ketut; Martadiani, A.A. Media; Sarmawa, I Wayan Gde (Jurnal Pendidikan Indonesia, 2024)
Globalization has had the impact of changes in the management of an organization, both business and non-business organizations. Every organization will survive if it has a competitive advantage. The research objective is to build sustainable competitive advantage in managing organizations in the education sector. This research explains how the knowledge management process, termed Knowledge Management, is influenced by business strategy mediation in increasing sustainable competitive advantage. Respondents are structural academic officials at private universities in Bali. The number of respondents was 100 people from 6 private universities in Denpasar. The sampling method uses non-probability purposive judgment sampling, where the sample is limited to structural officials in the academic field. This research uses descriptive and inferential statistics. Descriptive statistics are used to determine the characteristics of respondents and describe respondents' answers. Inferential statistics using Partial Least Square.to analyze data and test hypotheses.The research results show that the influence of Knowledge Management on business strategy and competitive advantage is positive and significant, business strategy mediates the influence of the KM process on competitive advantage. This means that the better the knowledge management process, the more relevant the strategies used, the more competitive advantage will increase. The implications of this research indicate that private higher education institutions in Bali need to adopt innovative strategic approaches to increase competitiveness.